Multimode vibrational coupling across the insulator-to-metal transition in 1T-TaS2 in THz cavities - Jarc, Giacomo; Mathengattil, Shahla Yasmin; Montanaro, Angela; Rigoni, Enrico; Dal Zilio, Simone; Fausti, Daniele (Journal of Chemical Physics, 2024)
The use of optical cavities on resonance with material excitations allows controlling light-matter interaction in both the regimes of weak and strong coupling. We study here the multimode vibrational coupling of low energy phonons in the charge-density-wave material 1T-TaS2 across its insulator-to-metal phase transition. For this purpose, we embed 1T-TaS2 into THz Fabry-Pérot cryogenic cavities tunable in frequency within the spectral range of the vibrational modes of the insulating phase and track the linear response of the coupled phonons across the insulator-to-metal transition. In the low temperature dielectric state, we reveal the signatures of a multimode vibrational strong collective coupling. The observed polariton modes inherit character from all the vibrational resonances as a consequence of the cavity-mediated hybridization. We reveal that the vibrational strong collective coupling is suppressed across the insulator-to-metal transition as a consequence of the phonon-screening induced by the free charges. Our findings emphasize how the response of cavity-coupled vibrations can be modified by the presence of free charges, uncovering a new direction toward the tuning of coherent light-matter interaction in cavity-confined correlated materials.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Coupled oscillators; Phase transitions; Phonons; Quasiparticle; Terahertz radiation; Linear response; Optical cavity